A new perspective to productivity measurement. (2nd January 2017) - Berhe, Ephrem; Abebe, Birhanu; Azene, Daniel
Abstract : Productivity has been practised by every company as a performance measure and indicator. It is broadly defined as the ratio of output values to input values. Usually, the total output value is represented by the sales revenue of conforming products, whereas the total input value constitutes all incurred costs, used or not. However, only those useful inputs are consumed by the conforming products. The remaining is not practically incorporated within the conforming products. This study intends to devise a new productivity measurement approach which discretely considers the effective and ineffective components of organisational inputs by taking advantage of the arithmetic inverse of the usual productivity ratio. The practicality of the new model is demonstrated in a selected manufacturing company and it is found that the inverse of the effective productivity is 0.58. This signifies that the company's productivity, if all inputs are efficiently used, can reach up until 1.72 – an inverse value of the inverted effective productivity. The cost of ineffective inputs is also found to be 23.2% of the total sales revenue. The new model can notably help decision-makers when working on the identification, measurement, and elimination of wastes from manufacturing processes.